Resilience and mobile phone addiction among adolescent athletes: a chain-mediated model of anxiety and depression - Tian, Feng; Zhang, Rong; Liu, Fengbo (Frontiers in Psychiatry, 2025)
BackgroundMobile phone addiction (MPA) has become a growing concern among adolescents, particularly within the group of adolescent athletes in high-pressure competitive environments. resilience may serve as a protective factor, but the underlying emotional mechanisms remain unclear. This study aimed to examine the mediating roles of anxiety and depression in the relationship between resilience and MPA among adolescent athletes.MethodsA total of 401 participants (aged 13–19) were recruited from a sports secondary school in Henan Province, China. Resilience, anxiety, depression, and MPA were measured using validated self-report scales. Structural equation modeling and bootstrap analysis (5,000 resamples) were conducted using Mplus 8.3.ResultsResilience was not significantly associated with MPA in the direct path. For the indirect path, the pathway from resilience to MPA through depression was significant, whereas the pathway through anxiety was not. And a significant chain mediation was found from resilience to MPA through both anxiety and depression. The total indirect effect was significant, while the direct effect was not.ConclusionResilience is associated with lower levels of MPA in adolescents, primarily through its impact on depressive symptoms, with anxiety playing an indirect role through depression. These findings suggest that interventions promoting resilience and reducing depression may help mitigate problematic phone use in youth.